2016
DOI: 10.1038/hdy.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid sterility and evolution in Hawaiian Drosophila: differential gene and allele-specific expression analysis of backcross males

Abstract: The Hawaiian Drosophila are an iconic example of sequential colonization, adaptive radiation and speciation on islands. Genetic and phenotypic analysis of closely related species pairs that exhibit incomplete reproductive isolation can provide insights into the mechanisms of speciation. Drosophila silvestris from Hawai'i Island and Drosophila planitibia from Maui are two closely related allopatric Hawaiian picture-winged Drosophila that produce sterile F 1 males but fertile F 1 females, a pattern consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…RNA-seq data for D. silvestris, D. heteroneura, and D. planitibia were downloaded from NCBI Gene Expression Omnibus (GEO, www.ncbi. nlm.nih.gov/geo) under accession number GSE80124 and from our previous study [Brill et al, 2016]. Adapters were removed from the raw sequencing reads.…”
Section: Gene Prediction and Annotationmentioning
confidence: 99%
“…RNA-seq data for D. silvestris, D. heteroneura, and D. planitibia were downloaded from NCBI Gene Expression Omnibus (GEO, www.ncbi. nlm.nih.gov/geo) under accession number GSE80124 and from our previous study [Brill et al, 2016]. Adapters were removed from the raw sequencing reads.…”
Section: Gene Prediction and Annotationmentioning
confidence: 99%
“…In many eukaryotic organisms, especially Drosophila, hybrid male sterility is a key event of post-zygotic reproductive isolating mechanism, and, our results of experimental hybridization between these two sibling species provides the evidence of preliminary post-zygotic reproductive isolation. In the present study, post-zygotic isolation might be the result of distorted interaction of genetic combination of the parental lineages that, although functional in their normal genetic backgrounds, reduce fitness when recombined in hybrids (Rundle, Nagel, Boughman, & Schluter, 2000;Burton, Ellison, & Harrison, 2006;Rogers & Bernatchez, 2006;Gow, Peichel, & Taylor, 2007). Several genes are involved in the expression of this complex and polygenic trait (Gomes & Civetta, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…In a long history of evolutionary biology, hybrid male sterility was studied extensively by using Drosophila as a model because Drosophila is particularly well suited to study such kind of reproductive barriers, as species within this genus are highly variable in degree of reproductive isolation from noninterbreeding species to hybridizing species (Yukilevich & True, 2008;Civetta & Gaudreau, 2015;Brill, Kang, K. Michalak, P. Michalak, & Price, 2016). Therefore, in the present study, we studied hybrid sterility between these two sibling species to understand the exact status of post-zygotic isolation by means of larval activity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clear importance of changes in gene expression for phenotypic evolution (Wittkopp, 2013), empirical support for regulatory divergence as a general driver of hybrid incompatibilities is mixed. While many studies have uncovered pervasive gene misexpression in sterile hybrids (Michalak & Noor, 2003; Ranz et al , 2004; Haerty & Singh, 2006; Malone et al , 2007; Coolon et al , 2014; Brill et al , 2016; Mack et al , 2016), others have found no association between patterns of gene expression and hybrid dysfunction (Barbash & Lorigan, 2007; Wei et al , 2014; Guerrero et al , 2016). Even when sterile or inviable hybrids do show misexpression, it is usually difficult to determine which is cause and which is effect.…”
Section: Introductionmentioning
confidence: 99%